Geography Core Courses and the Cultivation of Compound Talents: Exploring Innovative Paths - Dong, Liqin (International Journal of Natural Resources and Environmental Studies, 2024)
As an interdisciplinary and comprehensive science, geography plays a crucial role in cultivating innovative and interdisciplinary talents through its core courses. This paper analyzes the current state of geography core courses and explores how to optimize curriculum design, enhance practical teaching, and introduce innovative teaching methods to better meet societal demands for compound talents. Through data analysis and chart presentation, this paper further demonstrates the effectiveness and necessity of reform measures and discusses potential challenges in implementation, proposing corresponding countermeasures.